Immunohistochemical analysis of HSP-70 and IL-6 expression in rooster testes treated with Cucurbita moschata seed extract under heat stress condition - Rochmi, S. E.; Sofyan, M. S.; Achmad, A. B.; Pertiwi, H.; Residiwati, G.; Ihsan, I. S.; Tuska, H. S. A.; Supriyadi, S. (Journal of the Indonesian Tropical Animal Agriculture, 2025)
Heat stress is a major environmental factor that disrupts reproductive function in poultry, primarily by triggering oxidative stress and inflammation in testicular tissue. This study evaluated the influence of Cucurbita moschata(pumpkin seed) extract in mitigating the adverse effect of heat stress in roosters testes by regulating key markers, heat shock protein 70 (HSP70) and interleukin-6 (IL-6).Twenty-five adult roosters, aged one year, were divided into five groups: a non-stressed control group, a heat-stressed group without treatment, and three heat-stressed groups treated orally with 1600, 3200, or 6400 mg/kg body weight of the extract for 21 consecutive days. Immunohistochemical analysis revealed that heat stress led to marked increases in HSP-70 and IL-6 expression in the testes, reflecting cellular stress and inflammatory responses. Notably, administration of Cucurbita moschataextract attenuated these responses in a dose-dependent manner, with the 3200 and 6400 mg/kg doses showing the most significant reduction in protein expression. These findings highlight the potential role of Cucurbita moschataas a natural therapeutic agent to protect male reproductive function under heat stress conditions through its antioxidant and anti-inflammatory properties.